New Polyprenylated Acylphloroglucinol Derivatives and Xanthones From Hypericum wilsonii - Hao, Ji; Zhou, Tongxi; Ma, Yuanren; Deng, Jingtong; Cheng, Haitao; Wang, Qiang; Lin, Qinxiong; Yang, Xinzhou; Choi, Hoyoung (Frontiers in Chemistry, 2021)
Four new polyprenylated acylphloroglucinol derivatives, hyperwilone A-D (1-4), and two new xanthones, wilsonxanthone A (5) and wilsonxanthone B (6), together with eight known compounds were isolated from the aerial parts of Hypericum wilsonii. Their structures were expounded by comprehensive analysis of the 1D and 2D NMR spectra and HRESIMS. The relative configurations and absolute configurations of 1-6 were determined by NMR calculations and comparing their experimental and computed ECD data. All compounds were evaluated for GLUT4 translocation effects in L6 myotubes. Compound 5 showed the strongest GLUT4 translocation effects with 2.57 folds at a concentration of 30 μg/mL.